Synthesis of ultrathin porous C3N4-modified Co3O4 nanosheets for enhanced oxygen evolution reaction. (20th January 2021) - Wang, Huan; Liu, Yanming; Sun, Zhonghua; Ren, Jianhai; Zou, Xiaoran; Zhang, Chun-Yang
Highlights: We synthesize ultrathin porous C3 N4 -modified Co3 O4 nanosheets to construct the 1-C3 N4 /Co3 O4 /Ni foam hybrid electrode This hybrid electrode can significantly reduce the charge transfer length and improve the electron transportation. The intimate interaction of Co3 O4 with C3 N4 can induce a charge redistribution at the interface. This hybrid electrode exhibits an enhanced oxygen evolution reaction performance and good stability. Abstract: Oxygen evolution reaction (OER) plays important roles in energy storage and conversion technologies, but the sluggish kinetics of OER may result in a large overpotential, and thus there is urgent need for the exploration of new electrocatalysts with a low overpotential and good stability. In this research, we integrate the melamine-assisted alkaline cobalt carbonate (CoCH) nanosheets pyrolysis with high-temperature solid phase fusion to construct the 1-C3 N4 /Co3 O4 /Ni foam hybrid electrode with Co3 O4 ultrathin porous nanosheets as the host, trace C3 N4 as the guest, and Ni foam (NF) as the current collector. Benefiting from the unique structure, the obtained 1-C3 N4 /Co3 O4 hybrid nanosheets can significantly reduce the charge transfer distance between the catalysts to electron collector and improve the electron transportation during the OER process. Moreover, the intimate interaction of Co3 O4 with C3 N4 can induce a charge redistribution at the interface. Consequently, the 1-C3 N4 /Co3 O4 /NF hybrid electrode exhibits an enhanced OER performance (166 mV at 10 mAcm −2 ) and good stability, superior to the commercial RuO2 particles and the reported transition metal-based electrocatalysts. Graphical Abstract: Image, graphical abstract